HUBUNGAN INTERPRETASI HASIL RADIOLOGIS DENGAN KEJADIAN NYERI SENDI LUTUT - Edy Cahyady; Caesar Aulia (Jurnal Sains Riset, 2021)
Knee pain is a condition in which a person feels a pain sensation in the knee when doing activities, walking, or while still. Radiology is the study of the process of making images (imaging) of human organs using x-ray radiation. Radiology has a very important role in the field of medicine and the field of health services. This research is an analytic study with a cross sectional approach. This research was conducted by looking directly at the radiological picture that was already experienced in expertise. After the data was analyzed, it was found that respondents who experienced the most pain scales were severe pain (35.5%), moderate pain (32.3%), and mild pain (32.3%). The highest interpretation of radiological results was that there were no abnormalities (54.8%) and the least (3.2%). The chi-square test was performed and the value (P-value = 0.046) which means that there is a relationship between the interpretation of radiological results and the incidence of knee joint pain.Keywords: Knee pain, pain, Radiology